Kajian Filologis Kajian Flologis Serat Pangrembag Ewah-ewahan Rarantaman Arta ing Taun 1925 Karembag ing Wulan Dhesember 1924 - Fatimah, Amah; N., Yusro Edy (Sutasoma : Jurnal Sastra Jawa, 2020)
ABSTRACT Manuscript fiber Pangrembag Ewah-ewahan Rarantaman Arta ing Taun 1925 Karembag ing Wulan Dhesember 1924 is one of the collections of manuscripts of state documents on the financial budget that is stored in the Museum Radya Pustaka Surakarta. Manuscript Pangrembag Ewah-ewahan Rarantaman Arta ing Taun 1925 Karembag ing Wulan Dhesember 1924 has RP number 129-1 and is 22 pages. This manuscript is written using Javanese krama inggil language with inserted Javanese-Dutch absorption language. The purpose of this study presents the text ranging from the description of manuscripts, transliteration, text edits and the apparatus of criticism and translation. Research data is manuscripts Pangrembag Ewah-ewahan Rarantaman Arta ing Taun 1925Karembag ing Wulan Dhesember 1924. The method of research is a single standard edition script method. As for the translation of the text using free translation, so that the results of the translation easily understood by the reader. The results of this research is a valid edition of the text according to philological studies. There is also a critical and translation apparatus in Indonesian form. Key words : Philology, Rarantaman Arta, Text.